Kajian Maskulinitas dalam Ranah Sastra Indonesia: Analisis Bibliometrik - Ulya, Chafit; Mila, Nur Annisa Lailatul; Hartono, Tirza Marshanda (Kajian Linguistik dan Sastra, 2025)
The study of masculinity in Indonesian literature plays a crucial role in revealing the dynamics of maleidentity and its relationship with patriarchal culture. This research aims to map the patterns and trendsof studies on masculinity within the realm of Indonesian literature using a bibliometric approach. Datawere collected from Google Scholar using the keyword “maskulinitas dalam sastra Indonesia” within thetime range of 2015–2025 through the Publish or Perish application. A total of 92 relevant articles wereanalyzed using VOSviewer to visualize keyword networks and term developments. The analysis resultsshow a significant increase in the number of publications, particularly in 2023 and 2024. The most citedarticles discuss the reconstruction of masculinity in relation to gender equality and its representationacross various media, such as novels, films, folklore, and online comics. The most dominant keywordsare “masculinity,” “representation,” and “novel.” The bibliometric visualization illustrates a shift in thefocus of studies from basic gender and patriarchy concepts toward contemporary masculinity andpopular media issues. This study indicates that masculinity has increasingly gained attention in the fieldof Indonesian literary studies, with a growing tendency toward interdisciplinary thinking and popularmedia analysis. These findings are expected to serve as a starting point for deeper and more systematicresearch development in the fields of literary sociology and gender studies.